THE MEANING OF RELATIONSHIP QUALITY BY THE BUSINESS LEADERS: RESULTS OF A QUALITATIVE STUDY - Jacquemod, Juija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of this research is to investigate the perception of the importance of relationship quality between the organisational leaders and their subordinates. Qualitative study methodology is used, applying the Leader-member exchange (LMX) theory as a ground for the research. The paper argues the importance of attributing the LMX to the organisational micro-foundation. Results suggest that despite of understanding of the importance of respect, trust, loyalty and other organisational assets for building effective organisational culture and competitiveness in the market, the large-size organisational leaders are not familiar with the concept of quality of relationship. Therefore, highlighting this theory and stressing the importance of relationship is particularly important in the educational process while the preparation of future leaders takes place.